The genesis of the textile industry from adorned nudity to ritual regalia : the changing role of fibre craft and their evovling techniques of manufacture in the Ancient Near East from the Natufian to the Ghassulian /: the changing role of fibre craft and their evovling techniques of manufacture in the Ancient Near East from the Natufian to the Ghassulian. ([2020]) - Levy, Janet
No abstract available